Responses to Interest Rate Changes: A Comparison between Domestic and Foreign Commercial Banks in Malaysia - Kassim, Salina; Abdul Manap, Turkhan Ali (Faculty of Economics and Administration, University of Malaya, 2012)
This study aims to analyse the impact of interest rate changes on the domestic and foreign banks and determine its monetary policy implications. The study employed the impulse response functions and variance decomposition analysis based on the Vector Autoregression model to study the responses of major balance sheet items, namely deposit and loan to interest rate shocks based on Malaysian data from the period January 1997 to December 2006. The study found that domestic banks responded differently to interest rate shocks compared to the foreign banks. The different responses of the balance sheet items of the domestic and foreign banks show that the impact of tight monetary policy is uneven across the banking institutions. It also implies that the domestic banks could learn from the prudent risk management practices of the foreign banks that enable them to resume lending after a shorter lapse compared to domestic banks.